Gram-scale synthesis of splat-shaped Ag–TiO2 nanocomposites for enhanced antimicrobial properties - Jaber, Mohammad; Mushtaq, Asim; Zhang, Kebiao; Wu, Jindan; Luo, Dandan; Yi, Zihan; Iqbal, M. Zubair; Kong, Xiangdong (Beilstein Journal of Nanotechnology, 2020)
The control over contagious diseases caused by pathogenic organisms has become a serious health issue. The extensive usage of antibiotics has led to the development of multidrug-resistant bacterial strains. In this regard, metal-oxide-based antibacterial nanomaterials have received potential research interest due to the efficient prevention of microorganism growth. In this study, splat-shaped Ag–TiO2 nanocomposites (NCs) were synthesized on the gram scale and the enhanced antibacterial properties of TiO2 in the presence of silver were examined. The formation of Ag–TiO2 NCs was analyzed through various characterization techniques. The cell viability experimental results demonstrated that the Ag–TiO2 NCs have good biocompatibility. The antibacterial activity of the prepared Ag–TiO2 NCs was tested against the Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Escherichia coli (E. coli) bacterial strains. The Ag–TiO2 NCs exhibited promising and superior antibacterial properties compared to TiO2 nanospheres as confirmed by the bacterial growth and inhibition zone. The improvement in the antibacterial activity was attributed to the synergistic effect of the hybrid nature of TiO2 nanoparticles in the presence of Ag.
Keywords: antimicrobial properties; biomaterials; nanocomposites; silver nanoparticles; titanium dioxide